SAT0258 Synergetic b-cell immunomodulation with rituximab and belimumab is clinically effective in severe and refractory systemic lupus erythematosus – the synbiose proof-of-concept study. (15th June 2017) - Kraaij, T; Kamerling, SW; Rooij, E de; Daele, PL van; Bajema, I; Bredewold, OW; Huizinga, TW; Rabelink, TJ; Kooten, C van; Teng, YK
Abstract : Background: The pathogenesis of systemic lupus erythematosus (SLE) is characterized by B-cell hyperactivity leading to autoreactive plasma cells (PCs) that produce pathogenic autoantibodies and contribute to onset and maintenance of SLE. Therefore, novel treatment strategies in SLE are aimed at targeting autoreactive PCs. Rituximab (RTX) is used as off-label treatment in SLE and depletes CD20+ B-cells effectively, but is unable to deplete CD20- PCs. Belimumab (BLM), an anti-BAFF (B-cell activating factor) antibody, demonstrated efficacy in SLE as add-on therapy and resulted in reduction of B-cells and PCs. Objectives: Because RTX+BLM has potential to target autoreactive PCs, we designed an open-label, proof-of-concept study to assess the clinical efficacy and safety of RTX+BLM in severe, refractory SLE patients. Methods: A phase 2 proof-of-concept study, the SynBioSe study, was set up to treat severe, serologically active and refractory SLE patients with RTX following BLM. The following endpoints were assessed at 24 weeks: a) clinical efficacy by SLEDAI; b) immunological effects on B-cells and PCs by high sensitivity flow cytometry, immunoglobulins and autoantibody levels, and c) safety parameters. Results: The study included 11 severe, refractory SLE patients of which 10 had lupus nephritis and 1 patient had neuropsychiatric lupus with a median SLEDAI of 18 [range 8–29]. Treatment with RTX+BLM led to clinically significant improvement to a median SLEDAI score of 2 [0–13] (p=0.002). Low disease activity (SLEDAI <4) was achieved in 80%. Clinical response was achieved while tapering steroids from a median dose of 60 [0–60] to 7.5 mg [0–12.5] and concomitant mycophenolate (MMF) was tapered to zero in all patients. With respect to safety, 23 adverse events (AEs) were reported of which none were serious AEs, 8 mild infections and 2 hypogammaglobulinemia. Complement usage was restored in all patients with a median increase in C3 of 33% [range 8–133] and in C4 levels of 39% [9–266]. RTX+BLM led to reduction of anti-dsDNA antibodies, from median 120 IU/ml [18–505] to 35 IU/ml [10–374] (p=0.012). CD19+ B-cells were depleted throughout the complete follow up (from median 206*10 6 cells/L [range 21*10 6 -511x10 6 ] at screening to 5x10 6 [0–24x10 6 ] at 24 weeks, p=0.004), including transitional B-cells (from median 1.3x10 3 cells/L [1–1.3x10 4 ] at screening to 98.5 [0–3.4x10 3 ] at 24 weeks, p=NS). Importantly, total immunoglobulin levels only declined temporarily. The latter was further corroborated by transient reductions in CD3-CD38brCD27brCD20- PCs from median 1.6x10 6 cells/L [5.6x10 3 –1.1x10 7 ] to 1.5x10 5 cells/L [5.3x10 4 –1.3x10 7 ] at 12 weeks (p=NS). At 24 weeks, these PCs were restored to baseline levels (1.4x10 6 cells/L [9.2x10 4 –3x10 7 ]). Conclusions: This is the first study to demonstrate that RTX+BLM effectively reduced disease activity in severe, refractory SLE without raising major safety issues, while reducing other immunosuppressant drugs. Autoreactive PCs were specifically targeted by RTX+BLM. Therefore, combination therapy of RTX+BLM is a promising strategy in severe SLE. Trial registration:ClinicalTrials.gov NCT02284984 Disclosure of Interest: None declared